Hábitos de vida, condições de saúde e composição corporal em nipo-brasileiros em Maringá-Paraná - Back, Ivi Ribeiro (2018)
The migratory process contributes to routine changes and health conditions of a person, with new habits adjusments, which can be noticed between men and women and in different generations. To evaluate the health conditions, life habits and body composition of Japanese-Brazilian people living in the municipality of Maringá, Paraná. Cross-sectional study carried out in a Municipality of Southern Brazil. Data collection took place from March to December 2016 through an interview that addressed sociodemographic characteristics, living habits, health conditions and body composition assessment. Data were analyzed using descriptive and inferential statistics. 603 Japanese-Brazilians were evaluated, distributed in four generations: issei (3.15%), nissei (47.1%), sansei (42.6%) and yonsei (7.1%), aged between 18 and 91 years (mean of 49.2 years), being female little more than half (53.5%). Concerning the living habits: 94.6% do not smoke; 72.1% have a regular diet; 74.4% are sedentary or irregularly active; 55.9% do not use alcoholic beverages. There were higher odds and prevalence among males: smokers (p<0.001); consumption of alcoholic beverages (p<0.001); and poor eating habits (p=0.006). Regarding to the generations: significantly higher frequency by isseis and nisseis of physical activity (p=0.04), fruit (p<0.001) and vegetables eating (p<0.001). The chance of not exercising and having unsatisfactory/poor fruit consumption is almost twice as high among the sansei as among nissei subjects. The nissei, however, with indications of not presenting chronic diseases and changes in blood pressure. Regarding the self-reported health conditions, the prevalence of hypertensive patients was 29.0%; diabetics, 15.4%; and hypercholesterolemia/hypertriglycerides, 23.5%. Changes in blood pressure were assessed at the time of evaluation (p=<0.001); of self-reported hypertension (0.003). Women, on the other hand, presented higher prevalence in relation to family history for diabetes mellitus (p=0.008) and cholesterol/triglyceres (p=0.001). Regarding the generations, chronic autoimmune diseases (p <0.001) were found to be more frequent in issei and sansei subjects. Regarding the nutritional evaluation, there wer highlighted rates of overweight (42.5%) and a considerable portion with low weight (10.1%), according to BMI. The men also presented supremacy in overweight and obesity by both the body mass index (BMI) parameters (p<0.001) and those specific to the Asian population. Regarding the variables associated with overweight and obesity, it was evaluated for overweight: male (ORaj=1.85, CI=1.24-2.76); age group of 40 to 49 years (ORaj=2.27; CI=1.10-4.68); and 50 to 59 years (ORaj=2.17, CI=1.004-4.72); consumption of alcoholic beverage (ORaj=2.11; CI=1.07-4.16); presence of chronic disease (ORaj=1.59, CI=1.02-2.46). The factors associated with obesity were: male gender (ORaj=3.63; CI=1.78-7.40); presence of chronic disease (ORaj=4.13; CI=1.96-8.71); age group of 30 to 39 years (ORaj=4.74, CI=1.65-13.64) and 40 to 49 years (ORaj=2.89, CI=1.05-7.95); and, to be irregularly active (ORaj=2.73, CI=1.12-6.69). The PCT and GC% values indicated overweight in the four generations. The nissei and sansei presented a higher frequency of overweight according to BMI (p<0.001). Low risk of abdominal obesity was observed among the yonseis (p<0.001). Overweight according to BMI was 1.49 times higher among the Sansei. It was observed male life habits in which smokers, alcohol users and poor eating habits predominate. Regarding health conditions, men have a higher prevalence of hypertension. Women had a higher family history of diabetes mellitus and cholesterol/triglycerides. Regarding the generations, issei and nissei subjects present a higher prevalence of family history for diabetes mellitus and cholesterol/triglycerides. Regarding the nutritional evaluation, there were highlighted rates of overweight and a considerable amount with low weight according to BMI. Some risk factors have been shown to be associated with overweight and obesity among Japanese-Brazilians, indicating the need for practical interventions aimed at reducing body weight in this population. The male gender, age range of 30 to 49 years, use of alcoholic beverages and presence of chronic diseases are associated with overweight or obesity. Considering these differences allows the health team to direct educational activities and to carry out specific interventions for the precaution of risk factors for chronic not transmissible diseases